Review: Lessons Learned From Clinical Trials Using Antimicrobial Peptides (AMPs) - Dijksteel, Gabrielle S.; Ulrich, Magda M. W.; Middelkoop, Esther; Boekema, Bouke K. H. L. (Frontiers in Microbiology, 2021)
Antimicrobial peptides (AMPs) or host defense peptides protect the host against various pathogens such as yeast, fungi, viruses and bacteria. AMPs also display immunomodulatory properties ranging from the modulation of inflammatory responses to the promotion of wound healing. More interestingly, AMPs cause cell disruption through nonspecific interactions with the membrane surface of pathogens. This is most likely responsible for the low or limited emergence of bacterial resistance against many AMPs. Despite the increasing number of antibiotic-resistant bacteria and the potency of novel AMPs to combat such pathogens, only a few AMPs are in clinical use. Therefore, the current review describes i) the potential of AMPs as alternatives to antibiotics, ii) the challenges towards clinical implementation of AMPs and iii) strategies to improve the success rate of AMPs in clinical trials, emphasizing the lessons we could learn from these trials.